توجيه قراءة الامام نافع عند ابن عطية في تفسيره من خلال سورتي آل عمران والنساء - نماذج مختارة - - دغمة, سلوى (جامعة الوادي university of eloued, 2023)
يندرج هذا البحث ضمن عنوان " توجيه قراءة الامام نافع عند ابن عطية في تفسيره من خلال سورتي آل عمران والنساء - نماذج مختارة -" وهو يعالج الاشكال الأتي : كيف وجه ابن عطية قراءة الامام نافع؟ وماهو منهجه في ذلك ؟ وللاجابة على هذا الاشكال سلكت خطة تمثلت في ثلاث مباحث ، المبحث الاول والذي يمثل الشق النظري ، حيث أدرجت فيه : التعريف بمصطلح توجيه القراءات، ثم تطرقت الى ترجمة الامامين نافع براوييه ، وابن عطية ، ثم قمت بالتعريف بتفسير المحرر الوجيز، وأما المبحث الثاني : فتناولت فيه أهم المصادر التي إعتمد عليها ابن عطيه في توجيه القراءات ، ثم بينت منهجه في عرض القراءات وتوجيهها ، وفي الاخير ختمت بحثي بمبحث تطبيقي ثالث: خصصته لدراسة توجيهات ابن عطية حسب أنواع توجيهات القراءات من خلال نماذج من سورتي آل عمران والنساء ، ولقد خلصت في هذا البحث الى نتائج أهمها : تنوع منهج ابن عطية في عرض توجيه القراءات بين التصريح بلفظ التوجيه ومرادفاته ، وباللفظ الموحي."The title of ""this research is the reading orientation of Imam Nafaa ibn Atia to its management from Surat Al lmran and Souart A`nnissaa -selected models-"" which deals with the following problem: how did Ibn Atia guide the reading of Imam Nafaa ? And with what approach did this work ? To answer these questions, I followed a plan which represents three researches, the firest is the theoretical part about the study, where I incorporated the definition of orientation of the 3 readings, and then I moved on to the translation of the Imams: Nafaa with his two Raouis (narrators), and Ibn Atiaa, l have defined the Tafsir (justification / explanation) of El Moharrar El Wadjiz . In The second, I introduced the most important sources adopted by Ibn Atiaa to the orientation of the readings .In addition, I presented the methodology of exposing the readings and their orientations. At the end, I concluded my research with a third practical part that I specialize in the study of the orientations of Ibn Atiaa according to the types of orientation of the readings from the copies of surats Al Imran and A`nnissaa, In this research, I concluded the most important results: the diversity of approach in presenting the guidance of the readings between declaring the word guidance and its synonyms, and suggestive word."
التفسير
Keywords: توجيه القراءات، ابن عطية ، المحرر الوجيز ،الامام نافع; directing the reading, ibn atiaa , al muharraq al wajeez , imam nafaa